2016
DOI: 10.1007/s10334-016-0546-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional connectome of human brainstem nuclei of the ascending arousal, autonomic, and motor systems by high spatial resolution 7-Tesla fMRI

Abstract: Object To map the in vivo human functional connectivity of several brainstem nuclei with the rest of the brain by using seed-based correlation of ultra-high magnetic field functional magnetic resonance imaging (fMRI) data. Materials and Methods We used the recently developed template of 11 brainstem nuclei derived from multi-contrast structural MRI at 7 Tesla as seed regions to determine their connectivity to the rest of the brain. To achieve this, we utilized the increased contrast-to-noise ratio of 7 Tesla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 56 publications
8
63
0
1
Order By: Relevance
“…B). In TD, confirmatory whole brain correlation with post-error slowing activity in raphe nucleus replicated previous findings using PET and resting state fMRI (Beliveau et al, 2015;Bianciardi et al, 2016) of positive correlations in parahippocampus, anterior insula, ACC/OFC, superior temporal and precuneus, and negative correlations in bilateral pre/post/paracentral and left superior frontal gyrus (S7 Fig.). The only correlation from Beliveau et al (2015) that was not present in TD was with right superior parietal lobule.…”
Section: Raphe Nucleussupporting
confidence: 85%
See 3 more Smart Citations
“…B). In TD, confirmatory whole brain correlation with post-error slowing activity in raphe nucleus replicated previous findings using PET and resting state fMRI (Beliveau et al, 2015;Bianciardi et al, 2016) of positive correlations in parahippocampus, anterior insula, ACC/OFC, superior temporal and precuneus, and negative correlations in bilateral pre/post/paracentral and left superior frontal gyrus (S7 Fig.). The only correlation from Beliveau et al (2015) that was not present in TD was with right superior parietal lobule.…”
Section: Raphe Nucleussupporting
confidence: 85%
“…Our results also show that the low field large voxel approach can successfully identify rapidly changing connectivities with specific brainstem nuclei on errors in the SST. In particular, confirmatory whole brain correlation analyses with post-error slowing activity in SN and raphe nuclei were consistent with their known connectivity patterns, providing definitive evidence that these activities reflect the same kind of neurotransmitter function that has been identified with PET and time series analyses using high-field fMRI (Beliveau et al, 2015;Bianciardi et al, 2016), and rules out previous assertions that SN activity identified with this approach instead reflects subthalamic nucleus (Danielmeier and Ullsperger, 2011). LC is large enough to be detectable using low field large voxel fMRI (Chen and Ogawa, 1999) and has similar levels of neighboring noise (Brooks et al, 2013) and less distortion (Jezzard and Balaban, 1995;Napadow et al, 2006) than raphe nucleus across multiple field strengths.…”
Section: Methodological Considerationssupporting
confidence: 57%
See 2 more Smart Citations
“…These organized resting-state fluctuations are not an exclusively cortical phenomenon, but have also been observed in subcortical regions as low as the pons and medulla (Beissner et al, 2014;Bianciardi et al, 2016), raising the question whether they constitute a functional signature of the entire central nervous system and might thus be detectable in the spinal cord as well. However, answering this question is a difficult endeavour, because it is challenging to obtain reliable fMRI data from the spinal cord due to a number of issues (Giove et al, 2004;Summers et al, 2010), the most prominent of which are: 1) the spinal cord has a very small cross-sectional area (Fradet et al, 2014;Ko et al, 2004), 2) the detrimental influence of physiological noise from cardiac and respiratory sources is much more prominent in the spinal cord than in the brain (Piché et al, 2009;Verma and Cohen-Adad, 2014), and 3) signal loss and image distortion periodically occur along the spinal cord due to the different magnetic susceptibility of vertebrae and connective tissue (Cooke et al, 2004;Finsterbusch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%